Pengaruh Optimasi Biaya Produksi terhadap Peningkatan Keuntungan (Laba) pada UMKM di Pancing, Kota Medan - Yoga Saputra Manihuruk; Nadia Indah Lestari; Cindy Dwiana Putri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the effect of production cost optimization on increasing profits (profit) in Micro, Small, and Medium Enterprises (MSMEs) in Pancing, Medan City. MSMEs have an important role in the Indonesian economy, contributing around 60% of Gross Domestic Product (GDP) and absorbing more than 97% of the workforce. However, many MSMEs face challenges in managing production costs efficiently, which can reduce their profit margins and competitiveness in the market. The method used in this study was a survey with a questionnaire distributed to 10 registered MSME respondents. The results of the analysis showed that 80% of respondents had businesses registered as MSMEs, and 60% of them conducted production cost analysis regularly. In addition, 70% of respondents believed that good production cost management could increase their business profits. Correlation analysis showed a strong positive relationship between production cost optimization and increased profits, with a correlation coefficient of 0.75 and a significance value of p <0.05. The regression results showed that every one unit increase in production cost optimization would increase profits by 1.20 units. This study concludes that production cost optimization has a significant effect on increasing profits in MSMEs in Medan. Therefore, it is recommended that MSME owners continue to improve their understanding of the importance of production cost optimization and implement technology that can help efficiency and conduct cost analysis regularly.